Design and Implementation of a central control unit in an automotive drive-by-wire system - Angerd, Alexandra; JOHANSSON, ANDREAS (My University, 2013)
X-by-wire is a technique which is commonly used in aeronautics, but a challenge to face for the automotive industry. The objective of Sigma Kudos, which is a consultancy company in the automotive industry, is to implement a drive-by-wire system in a fullsize electric car. As part of the process of developing a prototype, the purpose of this project was to design a central control unit which would bring the prototype one step closer to vehicle implementation. In addition, the central control unit had to support an already existing system, containing throttle, brake, and steering functionality. To achieve this a platform was chosen, consisting of a TMS570 development board from Texas Instruments, and a GPL licensed FreeRTOS software platform from Real Time Engineers Ltd. The outcome of the project was an extensible platform with the potential of supporting full-size vehicles. However, questions arose regarding the use of an open source software platform in a safety-critical system, which is an issue that should be investigated further.
Keywords: Data- och informationsvetenskap; Informations- och kommunikationsteknik; Computer and Information Science; Information & Communication Technology